(E)-4-Methyl-N-((quinolin-2-yl)ethylidene)aniline as ligand for IIB supramolecular complexes: synthesis, structure, aggregation-induced emission enhancement and application in PMMA-doped hybrid material. Issue 1 (29th November 2016) - Wang, Ani; Fan, Ruiqing; Dong, Yuwei; Chen, Wei; Song, Yang; Wang, Ping; Hao, Sue; Liu, Zhigang; Yang, Yulin
Abstract : Complexes1–5 with AIEE properties were synthesized and1 was incorporated into PMMA. Abstract : Judicious structural design employing 2-quinolinecarboxaldehyde and 4-methylaniline was used to generate the Schiff base ligand ( E )-4-methyl- N -((quinolin-2-yl)ethylidene)aniline (L ). Five IIB complexes, namely, [ZnL Cl2 ] (1 ), [ZnL (NO3 )2 ] (2 ), [ZnL (OAc)2 ]3 (3 ), [CdL (OAc)2 ]3 (4 ), and [HgL Cl2 ] (5 ) have been synthesized based onL . Single-crystal X-ray diffraction analysis indicates that complexes1, 3 and4 exhibit 3D networks, whereas2 and5 form 2D layers and 1D chains, respectively. TD-DFT calculations show a good correlation with the UV-vis absorption assigned to π → π* intraligand transitions. Furthermore, complexes1–5 displayed strong greenish luminescent emissions (518–524 nm) in the aggregate state but weak emissions in solution (aggregation-induced emission enhancement), which may be due to the existence of C–H⋯Cl/O hydrogen bonding and π⋯π stacking interactions, resulting in restriction of intramolecular rotation (RIR). Variable-concentration 1 H NMR studies suggested that the aggregates undergo intramolecular changes in conformation due to intermolecular interactions. Moreover, the emission intensity and lifetime exhibited obvious increases induced by mechanical grinding and temperature reduction, which were also attributed to AIEE properties. Subsequently, complex1 was incorporated into poly(methyl methacrylate) (PMMA), whereby1 -PMMA exhibited enhanced emission intensity (20-fold increase in comparison with that of1 ), which offers opportunities for use in plastic greenhouses to increase leaf photosynthesis.